PERSEPSI MAHASISWA TERHADAP BAHAN AJAR BAHASA INGGRIS: STUDI KASUS MAHASISWA ETNIS TOMBULU DI FAKULTAS ILMU BUDAYA, UNIVERSITAS SAM RATULANGI - Ngala, Nikita Gratcia; Warouw, Maya P.; Wantasen, Isnawati L. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2021)
Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  ABSTRACTÂ  Â  Â The research is entitled â€œStudentsâ€™ Perceptions on ELT Materials: A Case Study of Students with Tombulunese Background in the Faculty of Humanities, Sam Ratulangi Universityâ€. The objectives of this research are to identify and to analyze about studentsâ€™ perceptions towards ELT Materials which, in this research, is Written 4 textbook. It is also to analyze and describe the factors that influenced their perceptions of the textbook materials. This research employs case study as an approach and uses a descriptive method. The writer collected the data by interviewing English Department students with Tombulunese background with a total of 6 participants from batch 2015 and 2016. As the result of this research, the writer has found sixteen perceptions based on Tomlinsonâ€™s theory of good textbook criterion, where two of them did not fulfill the criteria, and one perception of socio-cultural aspects in the textbook materials. In this research, the writer also found the factors that influenced their perceptions which consists of internal factors and external factors, they are; 1) interest, 2) needs, 3) background, 4) experience 5) culture 6) classroom environment.Keywords: Studentsâ€™ perception, English learning, ELT materials